Splenic participation in glycemic homeostasis in obese and non-obese male rats. Issue 5 (September 2020) - de Souza, Thainan A.; de Souza, Domwesley Wendreo; Siqueira, Bruna Schumaker; Rentz, Thiago; de Oliveria Emílio, Henriette Rosa; Grassiolli, Sabrina
Highlights: The spleen absence reduces body weight gain without to affect glucose homeostasis in Control (non-obese) rats. Hyperinsulinemia and glucose intolerance are reduced by splenectomy in MSG-obese rats. Glucose-induced insulin secretion is reduced in isolated pancreatic islets from MSG-splenectomized rats. Spleen influences glucose homeostasis in obese rats. Abstract: We evaluated the effects of splenectomy on glucose homeostasis in obese and non-obese rats. Obesity was induced by subcutaneous injections of monosodium glutamate (MSG; 4 g/kg) in neonatal rats. Control (non-obese) animals received equimolar saline. Splenectomy (SPL) was performed at 21 or 60 days of life (SPL21 and SPL60 ) in MSG obese and non-obese groups. Glucose tolerance, insulin resistance (IR), adiposity, histology of white adipose tissue (WAT) depots and glucose-induced insulin secretion (GIIS) in isolated pancreatic islets were evaluated at 90 days of life. In non-obese, despite of hyperphagia, the spleen ablation reduced body weight gain and energy efficiency, without changes in GIIS or IR. Slight reduction in glucose tolerance and augmented adipocyte size in subcutaneous WAT was noted in non-obese SPL21 group. In MSG-SPL21 rats was observed augmented body weight gain and energy efficiency, without alter adipocyte size. In contrast, MSG-SPL60 rats had lower body weight gain, reduced energy efficiency and smaller adipocyte size in WAT visceral depot in relation to MSG non-operated. Spleen ablation reduced insulin plasma levels in the MSG-SPL21 and MSG-SPL60 groups. Moreover, splenectomy reduced GIIS and improved glucose tolerance in MSG-SPL21 group. In MSG-SPL60 rats were observed reduction in IR, without changes in GIIS, despite of elevated glucokinase expression in pancreatic islets. In conclusion, spleen ablation reduces body weight in non-obese rats and slightly modifies glucose homeostasis. In contrast, in MSG-induced obesity, absence of the spleen can ameliorate glucose tolerance and reduce insulin secretion, improving insulin sensitivity.